INDENTIFIKASI SWAMEDIKASI PENGEMUDI ANGKUTAN UMUM DI KECAMATAN PARONGPONG KABUPATEN BANDUNG BARAT - Cindy Herliani Setiawan; Untung Sudharmono (Jurnal Skolastik Keperawatan, 2019)
Self-medication is the selection of medicines to treat symptoms and disorders of yourself without using a doctor's prescription. The perpetrators of self-medication came from various circles, including public transportation drivers. The purpose of this study is to identify self-transportation of public transport drivers in the Parongpong terminal, West Bandung Regency. This research method is quantitative descriptive. The sample in this study was taken by purposive sampling with 126 respondents who work as public transportation drivers. The results of this study found that 66% of respondents did self-medication and 34% of respondents did not do self-medication. All types of drugs used are found to be free in stalls, drug stores and pharmacies and have side effects that can cause a decrease in the concentration of the driver and can cause traffic accidents that can be detrimental to oneself even people around. Keywords: self-medication, side effects, public transport drivers.